SPL1 positively regulates cuticular ridge wax biosynthesis in Arabidopsis - Hui-Xian Zhu; Jia-Fa Huang; Jun-Feng Cao; Ling-Jian Wang; Jin-Quan Huang (Plant Stress)
The plant cuticle serves as a critical protective barrier against diverse environmental stresses. In various species, cuticles of sepals and petals display distinct ridge-like structures. However, the molecular mechanisms underlying the formation and maintenance of these cuticular ridges have remained enigmatic. Here, we elucidate that the production of cuticular ridge wax is regulated by SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) transcription factors in Arabidopsis. SPL1 and SPL12 double mutants (spl1spl12) exhibit severe defects in cuticular ridge formation, coupled with markedly reduced seed-setting rates and increased organ fusion compared to wild-type plants. Furthermore, we demonstrate that SPL1 positively regulate the expression of key enzymes involved in wax biosynthesis, including the alkane-forming enzymes ECERIFERUM1 (CER1), CER1-like (CER1L), and the primary (1-) alcohol-forming enzyme CER4. These enzymes are essential for the synthesis of alkanes and 1-alcohols, which are vital for the accumulation of cuticular ridge wax. Additionally, we identified that HSP70–16 interacts with SPL1, enhancing its transcriptional activity. Together, these results uncover a regulatory network essential for cuticular ridge formation and provide insights into plant developmental processes.